THE IMPLEMENTATION OF ENGLISH TEACHING PRACTICUM AT AL ISTIQAMAH BOARDING SCHOOL BANJARMASIN - Asfihana, Raida (English Department of Faculty of Tarbiyah and Teacher Training, 2014)
Language teachers are expected not only learn the theoretical knowledge such as grammar, linguistics, teaching methodology, curriculum, or assessment but also the practical knowledge on how to apply those theories in teaching. As candidate teachers, students from Faculty of Tarbiyah and Teacher Training need to feel the benefits of teaching practicum. The main purpose of this research is to describe the implementation of teaching practicum conducted by English Department students at Al Istiqamah boarding school Banjarmasin in the academic year of 2013/2014. Next, it focuses on the students? perception of teaching practicum, the role of mentor teachers at school, and the benefits they gained as well as the constraints that they faced during the two-month period of teaching practicum. This qualitative research takes 5 students teacher as the participants, respectively 2 students at MA and 3 students at MTs Al Istiqamah. The findings reveal that despite multiple challenges faced during teaching practicum, student teachers have positive perception towards the practice as they could learn how to adapt to various classroom situations. Student teachers tried to implement the theoretical knowledge from the coursework of English Department such as how to use appropriate media and apply various techniques in teaching. However, there are some constraints such as language skills, student behavior, limited school facilities, and lack of support from mentor teacher.